Exploring the hospitality industry - Walker, John R. 1944-; Walker, Josielyn T. (Pearson Prentice Hall, 2012)
This textbook offers broad coverage of the hospitality industry. It focuses not just on restaurants & hotels but on new growth areas such as event management, theme parks, attractions & entertainment. Each chapter features case studies, industry practitioners & corporate profiles that emphasise the real-world issues.